The bien r package: A tool to access the Botanical Information and Ecology Network (BIEN) database. Issue 2 (6th September 2017) - Maitner, Brian S.; Boyle, Brad; Casler, Nathan; Condit, Rick; Donoghue, John; Durán, Sandra M.; Guaderrama, Daniel; Hinchliff, Cody E.; Jørgensen, Peter M.; Kraft, Nathan J.B.; McGill, Brian; Merow, Cory; et al.
Abstract: There is an urgent need for large‐scale botanical data to improve our understanding of community assembly, coexistence, biogeography, evolution, and many other fundamental biological processes. Understanding these processes is critical for predicting and handling human‐biodiversity interactions and global change dynamics such as food and energy security, ecosystem services, climate change, and species invasions. The Botanical Information and Ecology Network (BIEN) database comprises an unprecedented wealth of cleaned and standardised botanical data, containing roughly 81 million occurrence records from c . 375, 000 species, c . 915, 000 trait observations across 28 traits from c . 93, 000 species, and co‐occurrence records from 110, 000 ecological plots globally, as well as 100, 000 range maps and 100 replicated phylogenies (each containing 81, 274 species) for New World species. Here, we describe an r package that provides easy access to these data. The bien r package allows users to access the multiple types of data in the BIEN database. Functions in this package query the BIEN database by turning user inputs into optimised PostgreSQL functions. Function names follow a convention designed to make it easy to understand what each function does. We have also developed a protocol for providing customised citations and herbarium acknowledgements for data downloaded through the bien r package. The development of the BIEN database represents a significant achievement in biological data integration, cleaning and standardization. Likewise, the bien r package represents an important tool for open science that makes the BIEN database freely and easily accessible to everyone.